Rancangan D-Optimal Model Gompertz dengan Maple - Widiharih, Tatik; Warsito, Budi (Department of Statistics, Faculty of Science and Mathematics, Universitas Diponegoro, 2017)
Gompertz model is used in many areas including biological growth studies, animal and husbandry, chemistry, and agricultural. Locally D-optimal designs for Gompertz models with three parameters is investigated. We used the Generalized Equivalence Theorem of Kiefer and Wolvowitz to determine D-optimality criteria. Tchebysheff system is used to decide that the D-optimal design is minimally supported design or nonminimally supported design. The result, D-optimal design for Gompertz model is minimally supported design with uniform weight on its support.Keywords:D-optimal, Generalized Equivalence Theorem, Tchebysheff System,Â Minimally Supported, Uniform Weight.